2015
DOI: 10.1016/j.nuclphysb.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

De Sitter space in gauge/gravity duality

Abstract: We investigate gauge/gravity duality for gauge theories in de Sitter space.More precisely, we study a five-dimensional consistent truncation of type IIB supergravity, which encompasses a wide variety of gravity duals of strongly coupled gauge theories, including the Maldacena-Nunez solution and its walking deformations. We find several solutions of the 5d theory with dS 4 spacetime and nontrivial profiles for (some of) the scalars along the fifth (radial) direction. In the process, we prove that one of the equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 67 publications
(148 reference statements)
0
28
0
Order By: Relevance
“…Indeed, the minimal value of the first term now is: 29) which is greater than V t2 = 3+c 3−c for any c ∈ (0, 1). To conclude, the requirement, that V (φ) is positive-definite, does not impose any further restrictions on the parameter space of our class of models.…”
Section: )mentioning
confidence: 98%
“…Indeed, the minimal value of the first term now is: 29) which is greater than V t2 = 3+c 3−c for any c ∈ (0, 1). To conclude, the requirement, that V (φ) is positive-definite, does not impose any further restrictions on the parameter space of our class of models.…”
Section: )mentioning
confidence: 98%
“…Under the constant-roll condition, one can solve equations exactly [5]. Thus, one can systematically find a certain class of constant-roll inflationary models which are compatible with the observational data [5][6][7]. Moreover, one can extend an idea of constant-roll inflation to teleparallel f (T ) gravity where the inflaton is coupled to the f (T ) [8].…”
Section: Introductionmentioning
confidence: 96%
“…Despite the stability issue, ultra-slow roll inflation has received considerable attention during the last several years in relation to the observed low-l anomaly of the CMB [2]. It was also understood recently how to construct a class of ultra-slow roll composite inflation models in the context of the gauge/gravity duality [3,4,5]. Much more importantly, [6] showed that a certain generalization of ultra-slow roll, called constant roll, can give a longlasting/stable expansion in addition to producing a scale invariant spectrum of scalar perturbations.…”
Section: Introductionmentioning
confidence: 99%